Using MOOCs to organise problem-based learning in the professional training of IT students - Spirina, Ye.A.; Gorbunova, N.A.; Samoilova, I.A. (The Education and Science Journal, 2024)
Introduction. The digital transformation of education plays a key role in the formation of in-demand IT specialists. In modern conditions, the method of problem-oriented learning is actively being introduced into the educational process of higher education and contributes to the formation of professional, communicative and digital competencies of IT students. Aim. The present research aimed to validate the incorporation of massive open online course (MOOC) components in the organisation of problem-oriented training for IT students to enhance their professional competencies. Methodology and research methods. The study was conducted over two academic years, beginning in 2022, at Academician E. A. Buketov Karaganda University. A total of 24 teachers participated in the specialised training of IT students, along with 86 students participated. At the first stage, a model was developed to integrate MOOCs into the structure of a specialised IT discipline within the framework of a specialised IT discipline, utilising problem-oriented learning. Additionally, the baseline level of students’ readiness to engage with MOOC courses was assessed. At the second stage, the effectiveness of utilising MOOC courses for implementing problem-oriented learning in the study of IT disciplines was assessed. At the third stage, the results were summarised and conclusions were drawn. Results and scientific novelty. The approaches to the organisation of problem-based learning in the preparation of IT students were defined. The use of Coursera MOOCs as the most convenient platform for studying IT courses was justified. A model of MOOC integration into the structure of an academic discipline in the organisation of problem-oriented learning was developed and experimentally tested. Practical significance. The results of an empirical study of student involvement in the use of MOOCs in problem-based learning prove the functionality of Coursera MOOC courses and their positive impact on the learning process. The feasibility of utilising MOOCs for implementing problem-oriented training aimed at developing students’ professional IT competencies is well-supported.
Использование МООК при организации проблемно- ориентированного обучения в профессиональной подготовке студентов IT-направления
Empleo de los MOOC en la organización del aprendizaje basado en problemas durante la formación profesional de los estudiantes con orientación en TI
Keywords: massive open online courses; MOOCs; problem-based learning; IT student training